Critical roles for WDR72 in calcium transport and matrix protein removal during enamel maturation. Issue 4 (29th March 2015) - Wang, Shih‐Kai; Hu, Yuanyuan; Yang, Jie; Smith, Charles E.; Nunez, Stephanie M.; Richardson, Amelia S; Pal, Soumya; Samann, Andrew C.; Hu, Jan C.‐C.; Simmer, James P.
Abstract Defects in WDR72 (WD repeat‐containing protein 72) cause autosomal recessive hypomaturation amelogenesis imperfecta. We generated and characterized Wdr72‐knockout/lacZ‐knockin mice to investigate the role of WDR72 in enamel formation. In all analyses, enamel formed by Wdr72 heterozygous mice was indistinguishable from wild‐type enamel. Without WDR72, enamel mineral density increased early during the maturation stage but soon arrested. The null enamel layer was only a tenth as hard as wild‐type enamel and underwent rapid attrition following eruption. Despite the failure to further mineralize enamel deposited during the secretory stage, ectopic mineral formed on the enamel surface and penetrated into the overlying soft tissue. While the proteins in the enamel matrix were successfully degraded, the digestion products remained inside the enamel. Interactome analysis of WDR72 protein revealed potential interactions with clathrin‐associated proteins and involvement in ameloblastic endocytosis. The maturation stage mandibular incisor enamel did not stain with methyl red, indicating that the enamel did not acidify beneath ruffle‐ended ameloblasts. Attachment of maturation ameloblasts to the enamel layer was weakened, and SLC24A4, a critical ameloblast calcium transporter, did not localize appropriately along the ameloblast distal membrane. Fewer blood vessels were observed in the papillary layer supporting ameloblasts. Specific WDR72 expression by maturation stage ameloblasts explained the observation that enamel thickness and rod decussation (established during the secretory stage) are normal in the Wdr72 null mice. We conclude that WDR72 serves critical functions specifically during the maturation stage of amelogenesis and is required for both protein removal and enamel mineralization.